Uji aktivitas antioksidan dan evaluasi fisik sediaan emulgel kombinasi ektraks daun kelor dan ekstrak daun karamunting - Adhi Gunawan; Annisa Fatmawati; Wahyu Yuliana Solikhah; Nafa Meilingga Putri; Baiq Husnul Hotimah (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Antioxidants can be used as skin care cosmetics by preventing the formation of new free radicals, neutralizing and avoiding chain reactions, thereby slowing down premature aging caused by damage skin. Emulgel is a topical preparation that has several advantages, including thixotropic, non-greasy, easy to spread, easy to clean, mild, easy to rinse, longer shelf life, transparent, and comfortable to use. The aim of this study was to form a combination of Moringa leaf (Moringa oleifera Lam) extract and Karamunting leaf extract into an emulsion dosage form and determine the antioxidant activity using the DPPH method. The emulgel base formulation uses Carbopol as a gelling agent and a combination of Moringa and Karamunting leaf (Melastoma malabathricum L.) extracts with various concentrations (25% : 75%, 50% : 50%, 75% : 25%). The results showed that the emulgel preparation combined with Karamunting leaf extract and Moringa leaf extract met all the physical test standards for the preparation, and the results of the antioxidant activity test showed that formula I had the highest antioxidant activity, with IC50 value is 40.07 ppm, which means it is a very strong antioxidant.